The application of Mississippi Protocol in superimposed pre-eclampsia patients with class 2 hemolysis, elevated liver enzymes, and low platelet count (HELLP) syndrome - Anak Agung Ngurah Jaya Kusuma (Majalah Obstetri dan Ginekologi)
HIGHLIGHTS